Studies on Encrypted Secret Data Storage Techniques Analogous to Steganography - Gurunath R , Debabrata Samanta (International Journal of Advanced Science and Technology, 2020)
Everyone has lots of data. All data may be valuable for someone. Data hiding is the most important part of every storage system. The data hiding is originated from a concept called Steganography, in this particular digital image is selected and which is to be transferred to the other side over insecure communication channel. Before sending the image the image is prepared in such a way that the secret information to be sent will be embedded inside the digital image and then it is made to travel along the image. In this research paper we discuss all the existing systems of steganography and a comparative study of different data hiding schemes would be addressed.